Pest management practices in cowpea: a review - Jackai, L.E.N.; Adalla, C. (1997)
Cowpea yields are known to be low in most parts of the tropics because of heavy insect pest problems. In Africa, cowpea growers do not generally use synthetic insecticides; however, in most parts of Asia, dependence on the use of insecticides is common, often with serious environmental consequences. Such misuse of insecticides on cowpen, coupled with low yields, has led to an intensive search for pest control options that will increase yields with l i t t l e or no input from insecticides, or biointensive integrated pest management (IPM). The major elements of this strategy include host plant resistance, use of beneficial organisms, agronomic practices, and (where adequate results are not obtained) some insecticide input, preferably from plant-based insecticides. This paper reviews the status of each of these interventions in cowpea production and discusses new initiatives in cowpea pest management. We also identify gaps in research and discuss options for developing IPM on cowpea.